EFEKTIFITAS UNDANG-UNDANG NO. 17 TAHUN 2008 TENTANG PELAYARAN TERHADAP KESELAMATAN PENUMPANG TRANSPORTASI LAUTPADA PT. ASDP FERRY CABANG KUPANG BOLOK - Shelvia Sipa Hekin; Stefanus Don Rade (INTELIGENSIA MEDIA, 2023)
Indonesia is a Maritime Country, where Indonesia's seas are wider than its land. Therefore, it is certain that there will be modes of transportation as facilities and infrastructure to support the movement of people. Therefore, the problem in this journal is how to organize the transportation of passengers in sea transportation, forms of protection and also make the existing regulations effective, namely Law No. 17 of 2008 concerning shipping for the safety of sea transportation passengers in this case conducting research on PT. ASDP Kupang Bolok Ferry Branch.The research method used in this study is normative juridical research, because this research originates from positive law by looking at its relevance in its application in society, then the data obtained is analyzed qualitatively. Normative qualitative, namely the data obtained after being systematically arranged to be analyzed qualitatively normatively in the form of descriptions, so that conclusions can be drawn to achieve clarity regarding the issues to be studied. The results of the literature will be used to analyze the data, then the data will be analyzed qualitatively normatively to answer the problems in this journal.The main conclusion that can be drawn from the writing of this journal is that with the promulgation of Law No. 17 of 2008, it has also regulated how legal protection for users of sea transportation services, which expressly prohibits carriers from being responsible at all or limited to losses incurred caused by the means of transportation, proof of the existence of a transportation agreement is a passenger ticket. As for the suggestion in writing this journal is to increase its ability to support its obligations as the executor of transportation, the carrier together with the community and the government must work together to realize this.